Association between Waste Management and HBV among Solid Municipal Waste Workers: A Systematic Review and Meta-Analysis of Observational Studies - Carmela Romana Natalina Corrao; Angela Del Cimmuto; Carolina Marzuillo; Emanuele Paparo; Giuseppe La Torre (The Scientific World Journal)
Aim. To conduct a systematic review of this relationship using available published observational studies in the field of solid municipal waste treatment. Methods. The review of the scientific literature was based on Medline and Scopus databases up to December 2012, using the keywords HBV, waste, solid, treatment, workers, disposal, and refuse in different combinations. Results. 160 studies were found and checked. Finally, 5 observational studies were considered suitable, all cross-sectional. The pooled proportion of HBs-Ag considering all the studies was 11% (95% CI: 5–21%), and considering the high quality studies only, this proportion was 14% (95% CI: 6–24%). The pooled proportion of HBs-Ab positivity among waste workers considering all the studies was 14.2% (95% CI: 1.4–37.2%), and considering the high quality studies only, this proportion was 24% (95% CI: 18–30%). The pooled proportion of HBc-Ab positivity among waste workers considering all the studies was 24% (95% CI: 6–49%). The pooled estimation of the risk of HBV positivity (HBsAg) among exposed was OR = 2.39 (95% CI: 0.88–6.52). Conclusion. In conclusion, waste workers need to be vaccinated against HBV infection since they are at risk of acquiring this infection through the exposure to potentially infected waste.